Penerapan Metode Fuzzy Weighted Product dalam Pengambilan Keputusan Penerima Kartu Jakarta Pintar SDN Lubang Buaya 11 Pagi Jakarta Timur - shidieq, faris majdie; Turmudi, Turmudi; Juhari, Juhari (Jurnal Riset Mahasiswa Matematika, 2024)
Fuzzy Multi-Attribute Decision Making (FMADM) is a helpful method in decision support systems, as it is used to identify the best options among several options that meet the selected requirements. Fuzzy Weighted Product (FWP) is a method found in the FMADM method. The FWP method uses the concept of sorting by multiplying  the criterion rating, whose weight is the power of each of the criterion values. The purpose of this study is to apply the FWP method in determining KJP recipients. The stages in the FWP method started from the decision-making criteria of 191 students which included a lot of parental income, parental employment, vehicle ownership, and many dependents. Furthermore, the data is processed using the fuzzy system  and after that the application of the FWP method to perform further calculations. The stages are determining the weight and match rating, transforming the data, calculating the value of alternative preference (S), and the relative value of alternative (V). The best results are determined by the highest relative preference value. The results can be used for decision-making for KJP recipients at SDN Lubang Buaya 11 Pagi East Jakarta and help overcome underprivileged students in school fees.